‘It Is You in My Picture!’ A Holistic Approach to Six-Year-Old Children’s Art Experiences - Granö Päivi; Turunen Serja (Wiley-Blackwell Publishing, 2022)
The case study is a part of the research and art-based developmental project Rinnalla (Side by Side) – Mentors of Arts- and Narrative-based Approaches as a Support for Social-Emotional Learning and Growth in Early Childhood Education, where arts and narrative-based methods were used to support children’s social-emotional growth in early childhood education. This research focuses on six-year-old children’s experiences of a fairy tale and music based on H.C. Andersen’s The Ugly Duckling. The research questions are: (1) How do children express the emotions they experience while listening to a fairy tale and music? (2) How do the children express and build their peer relationships through communication while drawing? The intervention was implemented in a preschool group of 15 children. The data included around 120 minutes of recorded video and 30 drawings. The holistic and context-sensitive interpretation method of visual analysis was used to analyse the data. The interpretation demonstrated the importance of peer relationships and offered insight into the context significance. By drawing together and telling small stories in a shared time and place, the children negotiated their roles within the small group. They strengthened friendships and built peer relations. The drawing situation probably exposed pre-existing tensions between the children, and the children showed interest, support, care, and willingness to welcome others. The music and fairy tale experiences allowed children to process emotions and share their current daily lives.